(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the development of logical thinking skills of senior school students in mother tongue lessons from both theoretical and practical perspectives. The study examines the pedagogical essence of the concept of logical thinking, its significance in personal development, and effective teaching methods applied in mother tongue education. In addition, the role of problem-based learning, analytical questioning, text-based activities, and interactive methods in fostering students’ independent and critical thinking is substantiated. The findings of the research contribute to increasing the effectiveness of developing logical thinking skills in mother tongue lessons.